Measurement of potential child labour: a methodological demographic proposal - Silva, Eliud (2011)
From a demographic and actuarial perspective a useful and simple method to make indirect estimates about child labour is proposed. Also, the proposal is particularized, if all the suggested information does not exist or is unavailable, and then we used it to the Mexican context for 2007. For this purpose we employed births records, life tables, multiple decrement life tables, statistics of the scholar population and through Lexis Diagram we illustrate the proposal. We compare our results with those obtained through Mexican National Surveys and conclude that the proposed method provides satisfactory results.